2011
DOI: 10.1080/ac.66.4.2126597
|View full text |Cite
|
Sign up to set email alerts
|

Plasma thrombin-activatable fi brinolysis inhibitor levels and Thr325Ile polymorphism as a risk marker of myocardial infarction in Egyptian patients

Abstract: TAFI Thr325Ile and its respective plasma protein level could have a contribution to MI risk in the Egyptian population.This could be helpful in refining a risk profile for coronary heart disease (CHD) patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 0 publications
2
12
0
Order By: Relevance
“…From the above analysis, we conclude that the rs3742264 G>A and rs1926447 C>T polymorphisms can affect the expression and activation of TAFI, which inhibits fibrinolysis and promotes thrombus formation, thereby participating in the progression of CCVDs. In accordance with our analysis, Kamal et al (2011) reported that the Thr/Ile and Ile/Ile genotypes of rs1926447 were more frequent in myocardial infarction patients than in the control group, indicating the association between the CPB2 gene polymorphism and the risk of myocardial infarction. Moreover, Biswas et al (2009) revealed a strong connection between the rs3742264 polymorphism and the development of pediatric stroke.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…From the above analysis, we conclude that the rs3742264 G>A and rs1926447 C>T polymorphisms can affect the expression and activation of TAFI, which inhibits fibrinolysis and promotes thrombus formation, thereby participating in the progression of CCVDs. In accordance with our analysis, Kamal et al (2011) reported that the Thr/Ile and Ile/Ile genotypes of rs1926447 were more frequent in myocardial infarction patients than in the control group, indicating the association between the CPB2 gene polymorphism and the risk of myocardial infarction. Moreover, Biswas et al (2009) revealed a strong connection between the rs3742264 polymorphism and the development of pediatric stroke.…”
Section: Discussionsupporting
confidence: 76%
“…An additional study was removed owing to a lack of data integrity. Ultimately, we obtained nine case-control research papers published between 2003 and 2013 that were of moderate-to-high quality (Zorio et al, 2003;Leebeek et al, 2005;Xu et al, 2008;Biswas et al, 2009;Si, 2010;Kamal et al, 2011;Shi et al, 2011;Sun et al, 2011;Tokgoz et al, 2013). The demographic information, baseline characteristics, and other features, and the methodological quality of the extracted studies are presented in Tables 1 and 2.…”
Section: Selection Of Eligible Studiesmentioning
confidence: 99%
“…7 Some studies have shown that increased TAFIa is a risk factor for ischemic stroke, acute myocardial infarction, and venous thrombosis. [8][9][10] Although not all thrombotic disorders will cause activation of TAFI. Coagulation activation in a baboon model of low-dose E. coli induces sepsis not accompanied by activated TAFI, while continuous TAFI activation up to 8 hours, is seen in coagulation activation seen by high-dose E. coli.…”
Section: Introductionmentioning
confidence: 99%
“…Cardiovascular risk factors were recorded as described previously [28]. Hypertension was defined if the patient was receiving anti-hypertensive drugs or blood pressure exceeded 140/90 mmHg in repeated measurements.…”
Section: Methodsmentioning
confidence: 99%